2016
DOI: 10.2217/nnm-2016-0244
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid-Decorated Polyamidoamine Dendrimer Mediates Selective Uptake and High Expression of Genes in Head and Neck Cancer Cells

Abstract: Aim: Folic acid (FA)-decorated polyamidoamine dendrimer G4 (G4-FA) was synthesized and studied for targeted delivery of genes to head and neck cancer cells expressing high levels of folate receptors (FRs). Methods: Cellular uptake, targeting specificity, cytocompatibility and transfection efficiency were evaluated. Results: G4-FA competes with free FA for the same binding site. G4-FA facilitates the cellular uptake of DNA plasmids in a FR-dependent manner and selectively delivers plasmids to FR-high cells, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…For example, an optimal amount of FA moieties (0.1–0.2 μmol FA/mg polymer) was reported, above which the uptake of FA-nanogels was gradually decreased [50]. Similarly, we found excess amount of G4-FA conjugates could suppress the cellular uptake of conjugates themselves, most likely due to the saturation of FR on the cell surface [53]. The fundamental understanding of FA-conjugated nanoparticles as targeting vectors can help investigators to better design drug delivery systems for the cancers with high FR expression.…”
Section: Fa-decorated Nanomedicinesmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, an optimal amount of FA moieties (0.1–0.2 μmol FA/mg polymer) was reported, above which the uptake of FA-nanogels was gradually decreased [50]. Similarly, we found excess amount of G4-FA conjugates could suppress the cellular uptake of conjugates themselves, most likely due to the saturation of FR on the cell surface [53]. The fundamental understanding of FA-conjugated nanoparticles as targeting vectors can help investigators to better design drug delivery systems for the cancers with high FR expression.…”
Section: Fa-decorated Nanomedicinesmentioning
confidence: 67%
“…Furthermore, we found G4-FA was preferentially taken up by HN12 (FR-high) but not U87 (FR-low) cells in a co-culture model. As a result, G4-FA showed a higher cytocompatibility and transfection efficiency than none targeted dendrimer in FR-high cells such as HN12 and T98 [53]. …”
Section: Fa-decorated Nanomedicinesmentioning
confidence: 99%
“…Gal-G5/CEH complexes (2.5, 5, 10, 20, 40 and 50, w/w) and G5/CEH (0.25, 0.5, 1, 2, 4 and 8, w/w) were prepared following a procedure described earlier [23, 42]. The complexes were mixed with loading buffer and loaded onto a 0.8 % agarose gel containing ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanistically, we found that G4-FA could be preferentially taken up by HN12 cells, in which folate receptor α (FRα) is highly expressed, compared to low FRα-expressing U87 cells. In addition, G4-FA competes with free FA for the FRα on the surface of HN12 cells and facilitates FR-dependent cellular uptake of complexed plasmid DNA [10]. …”
Section: Introductionmentioning
confidence: 99%
“…injection for administration of targeted therapy as it would allow substantial accumulation of nanoparticles at the tumor site and reduce toxicity to the normal tissues. Our recent work showed that G4-FA facilitated the entry of plasmid DNA into HN12 cells via FRα-mediated endocytosis at a rate much lower than that of non-specific absorptive endocytosis of plasmid mediated by unmodified G4 [10]. We hypothesized that a controlled slow tumor-specific cellular uptake mechanism would promote greater nanoparticle uptake in the tumor and enhance therapeutic effectiveness.…”
Section: Introductionmentioning
confidence: 99%